Finnish HLA studies confirm the increased risk conferred by HLA-B27 homozygosity in ankylosing spondylitis. Issue 6 (25th October 2005) - Jaakkola, E; Herzberg, I; Laiho, K; Barnardo, M C N M; Pointon, J J; Kauppi, M; Kaarela, K; Tuomilehto-Wolf, E; Tuomilehto, J; Wordsworth, B P; Brown, M A
Abstract : Objective: To determine the influence of HLA-B27 homozygosity and HLA-DRB1 alleles in the susceptibility to, and severity of, ankylosing spondylitis in a Finnish population. Methods: 673 individuals from 261 families with ankylosing spondylitis were genotyped for HLA-DRB1 alleles and HLA-B27 heterozygosity/homozygosity. The frequencies of HLA-B27 homozygotes in probands from these families were compared with the expected number of HLA-B27 homozygotes in controls under Hardy–Weinberg equilibrium (HWE). The effect of HLA-DRB1 alleles was assessed using a logistic regression procedure conditioned on HLA-B27 and case–control analysis. Results: HLA-B27 was detected in 93% of cases of ankylosing spondylitis. An overrepresentation of HLA-B27 homozygotes was noted in ankylosing spondylitis (11%) compared with the expected number of HLA-B27 homozygotes under HWE (4%) (odds ratio (OR) = 3.3 (95% confidence interval, 1.6 to 6.8), p = 0.002). HLA-B27 homozygosity was marginally associated with reduced BASDAI ( HLA-B27 homozygotes, 4.5 (1.6); HLA-B27 heterozygotes, 5.4 (1.8) (mean (SD)), p = 0.05). Acute anterior uveitis (AAU) was present in significantly more HLA-B27 positive cases (50%) than HLA-B27 negative cases (16%) (OR = 5.4 (1.7 to 17), p<0.004). HLA-B27 positive cases had a lower average age of symptom onset (26.7 (8.0) years) compared with HLA-B27 negative cases (35.7 (11.2) years) (p<0.0001). Conclusions: HLA-B27 homozygosity is associated with a moderately increased risk of ankylosing spondylitis compared with HLA-B27 heterozygosity. HLA-B27 positive cases had an earlier age of onset of ankylosing spondylitis than HLA-B27 negative cases and were more likely to develop AAU. HLA-DRB1 alleles may influence the age of symptom onset of ankylosing spondylitis.